Remote Sensing for Land Administration 2.0 - Koeva, Mila; Bennett, Rohan; Persello, Claudio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The reprint "Land Administration 2.0" is an extension of the previous reprint "Remote Sensing for Land Administration", another Special Issue in Remote Sensing. This reprint unpacks the responsible use and integration of emerging remote sensing techniques into the domain of land administration, including land registration, cadastre, land use planning, land valuation, land taxation, and land development. The title was chosen as "Land Administration 2.0" in reference to both this Special Issue being the second volume on the topic "Land Administration" and the next-generation requirements of land administration including demands for 3D, indoor, underground, real-time, high-accuracy, lower-cost, and interoperable land data and information.